CT OF FACE AND NECK MASSES IN CHILDREN - VISRUTARATNA, Pannee; KHONGPIBOONKIJ, Piyadara; SINGHAVEJSAKUL, Jesada; YOUSUKH, Aumnart (The ASEAN Journal of Radiology, 2023)
CT scans of 16 patients with face and/or neck masses were reviewed. These patients were diagnosed by histopathology or clinical follow up as having cystic hygromas (6 cases), hemangiomas (5 cases), benign lymphoepithelial parotid cysts (2 cases), plunging ranula (1 case), non-Hodgkin lymphoma (1 case), and plexiform neurofibromatosis (1 case). Cystic hygromas were seen as uniloculated or multiloculated cystic masses with septa of variable thicknesses. The masses were usually not discrete. Hemangiomas were characterized by intense enhancement. Children with human immunodeficiency virus and benign lymphoepithelial cysts had bilateral diffuse enlarged parotid glands with multiple small cysts. The plunging ranula appeared as a well-defined homogeneous cystic lesion extending from the sublingual to the submandibular region. The location, extent and internal characteristics of face and/or neck masses were determined by CT.